(untitled) (Patan Pragya, 2020)
Migration is a major area of population and development. This study identifies the trend and destination of foreign labor migration in Nepal. Nepal’s economy is associated with the increase in foreign employment trends. Although recent trends have shown continuous increase in the pattern, there is much uncertainty on how long the trend can sustain or at what levels. Studies suggest that the demand for labour migrants in GCC (Gulf Cooperative Council) countries and Malaysia will continue in the near future, although multiple factors (not just the demand in the international market) influence any one worker’s decision to opt for foreign employment. The overall increasing number of labour permits issued is only one aspect of the foreign employment trend. Understanding associated trends is also necessary from a national development point of view: foreign employment and national development. There is need for a more comprehensive understanding of how the benefits of foreign employment can be optimized for use in national development beyond 2019.